A Novel Approach to Model Earth Fissure Caused by Extensive Aquifer Exploitation and its Application to the Wuxi Case, China. Issue 3 (25th March 2018) - Ye, Shujun; Franceschini, Andrea; Zhang, Yan; Janna, Carlo; Gong, Xulong; Yu, Jun; Teatini, Pietro
Abstract: Initially observed in the semiarid basins of southwestern USA, earth fissures due to aquifer over‐exploitation are presently threatening a large number of subsiding basins in various countries worldwide. Different mechanics have been proposed to explain this process, such as differential compaction, horizontal movements, and fault reactivation. Numerical modeling and prediction of this major geohazard caused by overuse of groundwater resources are challenging because of two main requirements: shifting from the classical continuous to discontinuous geomechanics and incorporating two‐dimensional features (the earth fissures) into large three‐dimensional (3‐D) modeling domain (the subsiding basin). In this work, we proposed a novel modeling approach to simulate earth fissure generation and propagation in 3‐D complex geological settings. A nested two‐scale approach associated with an original nonlinear elastoplastic finite element/interface element simulator allows modeling the mechanics of earth discontinuities, in terms of both sliding and opening. The model is applied on a case study in Wuxi, China, where groundwater pumping between 1985 and 2004 has caused land subsidence larger than 2 m. The model outcomes highlight that the presence of a shallow (∼80 m deep) bedrock ridge crossing the Yangtze River delta is the key factor triggering the earth fissure development in this area. Bending of the alluvial deposits around the ridge tip and shear stress due to the uneven piezometric change and asymmetrical shape of the bedrock have caused the earth fissure to onset at the land surface and propagate downward to a maximum depth of about 20–30 m. Maximum sliding and opening are computed in the range of 10–40 cm, in agreement with the order of magnitude estimated in the field. Key Points: An original approach shifting from the classical continuous to discontinuous geomechanics An original two‐scale modeling approach The first numerical simulation of an earth fissure development in a real case